Distopía tecnolóxica ou apocalipse zombi? Pasado ou presente? En DX de Eli Ríos - Garrido González, Ana (Madrygal. Revista de Estudios Gallegos, 2023)
The aim of this article is to analyse the novel DX by Eli Ríos (Urco, 2018), focusing on how the author elaborates on the genre of a dystopian novel with an almost apocalyptic ending which constitutes a clear anti-capitalist proclamation. However, the structure of the novel does not meet the reader's expectations. Eli Ríos follows Rafael Dieste's theory of the short story and applies techniques and elements that belong to the realm of the bizarre, fantastic, or even to survival horror video games. Thus, the two protagonists move through a realistic, familiar, and everyday space that sometimes becomes dark and labyrinthine. However, against all odds, the partners (of unknown sex and gender), manage to overcome the 'zombie' threat by means of consensus and the collaboration typical of an egalitarian love story full of eroticism and sensuality. It constitutes a deconstruction of gender roles and a parody of the heteronormativity characteristic of the heroic narrative, which might be read in line with Preciado's Manifesto Contrasexual.
Keywords: Fantastic; gender; Science Fiction; Sex discrimination.; zombies